Prosaics and Other Provocations Empathy, Open Time, and the Novel - Morson, Gary Saul (Ars Rossica, 2013)
Gary Saul Morson's ideas about life and literature have long inspired, annoyed, and provoked specialists and general readers. His work on "prosaics" (his coinage) argues that life's defining events are not grand but ordinary, and that the world's fundamental state is mess. Viewing time as a "field of possibilities," he maintains that contingency and freedom are real. To represent open time, some masterpieces have developed an alternative to structure and require a "prosaics of process." Morson's curmudgeonly alter ego, Alicia Chudo, invents the discipline of misanthropology," which explores human voices from voyeurism to violence. Reflecting on his legendarily popular courses, Morson argues that what literature teaches better than anything else is empathy. Himself an aphorist, Morson offers a witty approach to literature's shortest genres and to quotation in general.